2018
DOI: 10.1002/anie.201802003
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐ and Tissue‐Based Proteome Profiling and Dual Imaging of Apoptosis Markers with Probes Derived from Venetoclax and Idasanutlin

Abstract: Venetoclax (ABT-199) and idasanutlin (RG7388) are efficient anticancer drugs targeting two essential apoptosis markers, Bcl-2 and MDM2, respectively. Recent studies have shown that the combination of these two drugs leads to remarkable enhancement of anticancer efficacy, both in vitro and in vivo. In an attempt to disclose the relationships of their protein targets, competitive affinity-based proteome profiling coupled with bioimaging was employed to characterize their protein targets in the same cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Importantly, these approaches can be integrated with phenotypic screening as reported by our group and others, to accelerate the mechanistic characterization of screening hits. Moreover, we have endeavored to apply these approaches to study the protein targets of combination drugs, which provided useful information in understanding their synergistic effects . Meanwhile, a suite of fluorescent probes was developed to image cancer/apoptosis markers .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, these approaches can be integrated with phenotypic screening as reported by our group and others, to accelerate the mechanistic characterization of screening hits. Moreover, we have endeavored to apply these approaches to study the protein targets of combination drugs, which provided useful information in understanding their synergistic effects . Meanwhile, a suite of fluorescent probes was developed to image cancer/apoptosis markers .…”
Section: Figurementioning
confidence: 99%
“…[12] Meanwhile, as uite of fluorescent probesw as developed to image cancer/apoptosis markers. [10,12] These effortsh ave improved the applications of AfBP and bioimaging approaches in drug discovery and cancer-related diagnoses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[43] Recent work also demonstratedt hat ABPP can be appliedi n the study of underlying mechanism of combination drugs. [44] Venetoclax (ABT-199) and idasautlin (RG7388) are two first-inclass anticancer drugs targeting two essential apoptosis markers, Bcl2a nd MDM2. Recently,s everals tudies have shown that the combination of these drugs leads to remarkable synergistic anticancer activity.I no rder to understandt he underlying mechanism of this therapeutic strategy ande xplore their cellular off-targets, as uite of probes weres ynthesized by introducing am inimalist photocrosslinker or fluorophore directly into the original compounds (Figure 4, AB1/2 and RG-1), enabling simultaneous ABPP and bioimaging studies in cancerc ells and tumor tissues.As eries of protein hits including ITPR1, GSR, RER1, PDIA3,A poa1 and Tnfrs17 were successfully identified by pull-down/LC-MS/MS and confirmed by pull-down/WB and enzymatic assays,w hich can identify potentialo ff-targets and the reasons underlying synergistic effects.…”
Section: Targetidentification Of Bioactive Moleculesmentioning
confidence: 99%
“…So far, probes with PGs or “minimal” linkers, so called affinity‐based probes (AfBPs), have succeeded in labeling, enriching, and enabling the identification of many noncovalently interacting enzyme targets, including methyltransferases and kinases . However, in contrast with the success associated with creating many kinase‐labeling probes, the probes for profiling protein–protein‐interaction (PPI) targets are rather limited …”
Section: Introductionmentioning
confidence: 99%